2023
DOI: 10.3390/gels9070556
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Patents and Innovative Biopolymer-Based Hydrogels

Abstract: Biopolymers represent a great resource for the development and utilization of new functional materials due to their particular advantages such as biocompatibility, biodegradability and non-toxicity. “Intelligent gels” sensitive to different stimuli (temperature, pH, ionic strength) have different applications in many industries (e.g., pharmacy, biomedicine, food). This review summarizes the research efforts presented in the patent and non-patent literature. A discussion was conducted regarding biopolymer-based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 126 publications
0
9
0
Order By: Relevance
“…Initially, polymer properties are the most important factor for providing a wide variety of drug controlled-release profiles, including drug sustained release [ 70 , 71 , 72 , 73 , 74 ]. Numerous reports in the literature have demonstrated that insoluble and biodegradable polymers and their composites and hybrids can be exploited as carriers to manipulate the gradual release of the loaded drug molecules [ 75 , 76 , 77 , 78 ].…”
Section: Resultsmentioning
confidence: 99%
“…Initially, polymer properties are the most important factor for providing a wide variety of drug controlled-release profiles, including drug sustained release [ 70 , 71 , 72 , 73 , 74 ]. Numerous reports in the literature have demonstrated that insoluble and biodegradable polymers and their composites and hybrids can be exploited as carriers to manipulate the gradual release of the loaded drug molecules [ 75 , 76 , 77 , 78 ].…”
Section: Resultsmentioning
confidence: 99%
“…Soft porous natural materials represent very suitable materials for drug delivery systems, and silk-based biomaterials have shown different possibilities for tailoring such systems [ 3 , 91 , 103 , 109 , 125 ], including in the scope of bone tissue engineering [ 8 ]. Silk fibroin has shown good adjustability to suit different drug delivery systems, including hydrogels [ 116 , 117 , 121 ] or coatings and thin films [ 103 ]. Bioactivity and in vivo responses of silk proteins are important properties of the silk-based materials, utilized in this sense for tissue growth and remodeling [ 29 , 135 ].…”
Section: Spider Silk In Nanomedicinementioning
confidence: 99%
“…Small-molecule delivery systems have revolutionized materials science, agriculture, and biomedical research, offering an unparalleled ability to finely control the release kinetics of bioactive compounds [ 1 , 2 , 3 ]. Biopolymer-based controlled-release systems, among various strategies, have gained significant attention [ 4 , 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%